2022
DOI: 10.5435/jaaosglobal-d-21-00263
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Obese Patients Undergoing Revision Total Knee Arthroplasty: Understanding Demographics, Comorbidities, and Propensity Weighted Analysis of Inpatient Outcomes

Abstract: Introduction:Obesity is a public health epidemic that is projected to grow in coming years. Observational data on the epidemiologic profile and immediate postoperative outcomes of obesity and morbid obesity after revision total knee arthroplasty (rTKA) are limited.Methods:Discharge data from the National Inpatient Sample was used to identify patients who underwent rTKA from 2006 to 2015. Patients were stratified into morbidly obese, obese, and not obese control cohorts. An analysis was performed to compare eti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…27 Multiple studies in the literature report worse outcomes and increased complications among obese patients undergoing either primary or revision arthroplasty, as compared with nonobese patients. 6,28 Current research postulates that there exists a J-shaped curve correlating BMI with complications after revision TJA, suggesting a substantial increase in complications in morbidly obese patients, as BMI gets increasingly higher. 29 In addition, studies have shown increased risk for need for revision arthroplasty among obese patients, pointing to a potential compounding effect when obesity and frailty coexist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Multiple studies in the literature report worse outcomes and increased complications among obese patients undergoing either primary or revision arthroplasty, as compared with nonobese patients. 6,28 Current research postulates that there exists a J-shaped curve correlating BMI with complications after revision TJA, suggesting a substantial increase in complications in morbidly obese patients, as BMI gets increasingly higher. 29 In addition, studies have shown increased risk for need for revision arthroplasty among obese patients, pointing to a potential compounding effect when obesity and frailty coexist.…”
Section: Discussionmentioning
confidence: 99%
“…21, 783.22), muscular wasting and disuse atrophy (728.2), senility without mention of psychosis (797), malaise and fatigue (780.79), as validated in previous studies. [6][7][8][9][10][11][12][13] The inverse probability of treatment weighting with complex survey data was used to minimize confounding bias and adjust for comorbidity severity. Propensity score weighting was done per the method of DuGoff et al 7 by weighting patient demographics, hospital characteristics, reason and type of revision, and comorbidities using a modified version of the Elixhauser Comorbidity Index (ECI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge, this is the first analysis of complications after rTKAs in patients with HCV. As these patients often have more comorbidities than most patients undergoing an rTKA and higher comorbidity burdens are associated with an increased complication risk [ [41] , [42] , [43] , [44] ], medical optimization before an rTKA is critical in this population. Recent analyses have reported improved outcomes after a primary arthroplasty in patients with HCV who received preoperative antiviral treatment [ 16 , [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary total hip arthroplasty (THA) constitutes the standard of care for treatment of end-stage hip osteoarthritis and provides pain relief and improved joint function [ 1 ]. The prevalence of THA in the United States among adults fifty years of age or older was estimated to be 2.34% in 2010.…”
Section: Introductionmentioning
confidence: 99%